The Rich Man and Lazarus: The Parable and the Parallels - Bauckham, Richard 1946- (1991)
The interpretation of the parable of the rich man and Lazarus (Luke 16. 19–31) shows both how misleading extra-biblical parallels to biblical motifs can be when misused, and also how enlightening they can be when correctly used. The parable makes use of two major narrative motifs which can be paralleled in other ancient literature: (1) a reversal of fortunes experienced by a rich man and a poor man after death; (2) a dead person's return from the dead with a message for the living. Since Gressmann's monograph drew attention to one important example of (1) – the Egyptian story of Setme and Si-Osiris (together with later Jewish stories derived from it) – much discussion of the parable has been dominated by this one parallel. Both the way in which this parallel has been used in the interpretation of the parable and the restriction of interest to this one parallel have had unfortunate consequences.